IMPLEMENTASI STRATEGI BISNIS DIGITAL TERHADAP BISNIS DROPSHIPPING - Ahmad Alvin Adriansyah; Ayu Shintiya; Nadhila Nazlah Nst; Zahrani Fatni Hapsah; Nurbaiti Nurbaiti (JURNAL ILMIAH NUSANTARA, 2025)
Increasingly tight business competition means that many business people have to sharpen their business strategies to compete in this digital era. Likewise, dropshipping business players are increasing. The purpose of this research is to determine the implementation of digital business strategies in dropshipping businesses. This research uses a literature study approach using qualitative descriptive methods. The data used in this research is based on the results of previous studies that have been carried out and published in national and international online journals. The data collection process was also carried out by filtering several criteria set by the author with the keywords "digital business" and "dropshipping" from online articles. The results of this research show that a business strategy that is suitable for use in the dropshipping business is using a digital business strategy which includes selling online and using digital applications as well as implementing digital marketing by using social media and digital platforms to promote products such as Instagram, Shopee, Tiktok Shop, Tokopedia, Lazada and others. By utilizing paid advertising, engaging content, dropshippers can increase visibility and attract more customers.